A method for preparing water-stable all-inorganic cesium lead bromine perovskite nanoribbons by interfacial phase transformation
Through the interfacial phase transition-water initiation conversion method, the all-inorganic cesium lead bromine perovskite nanoribbon is stably dispersed in polar solvents, solving the problem of insufficient stability and dispersion of CsPbBr3 nanoribbon in aqueous solution in the prior art. High dispersion and good fluorescence performance are achieved, and the carrier migration and mechanical properties of the nanoribbons are enhanced.
Patent Information
- Application Number
- CN202211563993.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-07
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-12-07
AI Technical Summary
The prior art is difficult to stabilize and uniformly disperse all-inorganic cesium lead bromine perovskite nanocrystals in polar solvents, especially the preparation method of CsPbBr3 nanoribbons is complex and uses toxic reagents, and the stability of CsPbBr3 nanocrystals in aqueous solution and Inadequate dispersion.
The interface phase transition-water initiation conversion method was adopted to prepare a reaction solution of cesium precursor solution and lead bromide containing reaction solution by heat injection. After the reaction was added, anti-solvent and non-polar solvent were added for washing, and then Cs4PbBr6 nanocrystals were placed in two phases. The interface undergoes phase transformation and converts into a CsPbBr3 nanoribbon that is stably dispersed in water.
The high dispersion and stability of CsPbBr3 nanoribbons in water are achieved, good fluorescence performance is maintained, and the carrier migration and mechanical properties of the nanoribbons are improved, which is suitable for optoelectronic devices.
Smart Images

Figure CN116285978B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanomaterial preparation, and particularly relates to a method for preparing water-stable all-inorganic cesium lead bromine perovskite nanobelts through interfacial phase transformation. Background Art
[0002] The chemical composition of all-inorganic cesium lead halide perovskite nanocrystals is CsPbX3, where X = Cl, Br or I. It is a new type of fluorescent material that has become popular in recent years. Research has found that all-inorganic cesium lead halide perovskite nanocrystals have the advantages of high color purity, adjustable emission wavelength (410nm~760nm), narrow half-peak width (12nm~42nm), high fluorescence quantum yield (up to more than 95%) and full solution processing. It has broad application prospects in light-emitting diodes, solar cells, photocatalytic reduction of CO2, lasers and other fields.
[0003] At present, the synthesis methods of all-inorganic cesium lead halide perovskite nanocrystals (CsPbX3) that have been studied mainly include liquid phase chemical synthesis and physical vapor deposition (liquid phase chemical synthesis mainly includes high temperature hot injection method, room temperature coprecipitation method, solvent thermal synthesis method and microwave assisted synthesis method, etc.). The above methods all directly synthesize CsPbX3 products through a certain reaction process. The obtained perovskite nanocrystals can only be dispersed in non-polar solvents such as n-hexane and toluene, which greatly limits the application of perovskite nanocrystals in polar solvents; perovskite nanocrystals still have the problem of not being able to exist stably and not being able to be uniformly dispersed in aqueous solution. The existing invention patent with publication number CN109264771B prepares CsPbBr3 nanocrystals dispersed in non-polar solvents through a water-initiated process. The CsPbBr3 nanocrystals are dispersed in non-polar solvents, rather than in polar solvents. Therefore, it is necessary to develop a preparation technology for CsPbBr3 nanocrystals that can be stably dispersed in polar solvents (such as aqueous solutions). In addition, there are currently few reports on the preparation of CsPbBr3 nanobelts. The existing preparation methods for CsPbBr3 single-crystal nanowires with relatively large aspect ratios (such as the invention patent with publication number CN111139518A) not only require the use of toxic reagents such as acetone and N,N-dimethylformamide, but also have cumbersome operation processes and experimental cycles of more than 24 hours, wasting human and financial resources. Summary of the Invention
[0004] In response to the problems existing in the prior art, the present invention proposes a method for preparing water-stable all-inorganic cesium lead bromine perovskite nanobelts by interfacial phase transition. The purpose is to provide a phase transition-water-induced transformation method to prepare CsPbBr3 nanobelts that are uniformly dispersed in aqueous solution and have good stability, so that they have high dispersibility, high stability and good luminescence performance.
[0005] The present invention proposes a method for preparing water-stable all-inorganic cesium lead bromine perovskite nanoribbons by interfacial phase transformation, comprising the following steps:
[0006] (1) preparing a cesium precursor solution and a reaction solution containing lead bromide;
[0007] (2) adding a cesium precursor solution to a reaction solution containing lead bromide by a hot injection method, and cooling the mixture in an ice water bath after sufficient reaction to obtain a reaction mixture solution;
[0008] (3) adding an equal volume of antisolvent to the reaction mixture, centrifuging and removing the supernatant to obtain a Cs4PbBr6 precipitate mixture;
[0009] (4) adding a non-polar solvent to wash the Cs4PbBr6 precipitate mixture, washing and centrifuging multiple times to obtain a Cs4PbBr6 precipitate, and dispersing the Cs4PbBr6 precipitate in a non-polar solvent to obtain a Cs4PbBr6 nanocrystal dispersion solution;
[0010] (5) slowly injecting the Cs4PbBr6 nanocrystal dispersion solution into an equal volume of polar solvent, shaking vigorously, and then allowing the solution to stand and separate to obtain a CsPbBr3 nanocrystal solution;
[0011] (6) Use high-purity water to centrifuge and wash the CsPbBr3 nanocrystal solution to obtain CsPbBr3 nanobelts.
[0012] Specifically, the preparation method of the cesium precursor solution in step (1) is as follows: 0.16 g (0.49 mmol) of cesium carbonate is dissolved in 0.5 mL of oleic acid and 8 mL of N-methylpyrrolidone, the mixture is evacuated to a vacuum environment at 120° C., and then heated under a nitrogen atmosphere to fully dissolve the cesium carbonate, thereby obtaining a cesium precursor solution;
[0013] Specifically, the preparation method of the reaction solution containing lead bromide in step (1) is as follows: 0.188 mmol to 0.282 mmol (0.069 g to 0.103 g) of lead bromide is dissolved in 0.5 mL of oleic acid, 0.5 mL of oleylamine and 5 mL of N-methylpyrrolidone, first evacuating the mixture to a vacuum environment at 120° C., and then heating the mixture under a nitrogen atmosphere to obtain a reaction solution containing lead bromide;
[0014] Specifically, the temperature of the cesium precursor solution during the heating treatment is 150°C;
[0015] Specifically, the temperature of the lead bromide-containing reaction solution during the heating treatment is 160° C. to 170° C.;
[0016] Specifically, the amount of the cesium precursor solution added in step (2) is 0.4 mL to 0.6 mL;
[0017] Specifically, the antisolvent in step (3) is one of ethyl acetate, acetone, methanol, and acetonitrile;
[0018] Specifically, the non-polar solvent in step (4) is n-hexane solvent;
[0019] Specifically, the polar solvent in step (5) is distilled water.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The present invention uses a phase transition-water-induced conversion method to convert non-fluorescent Cs4PbBr6 nanocrystals dissolved in a non-polar solvent into fluorescent CsPbBr3 nanobelts that can be stably dispersed in water through phase transition at the two-phase interface. Moreover, when the two phases of non-polar solvent and water exist, the CsPbBr3 nanobelts can still maintain their green fluorescence well over time and have good water stability.
[0022] 2. Compared with three-dimensional structured nanocrystals, the size-related properties of perovskite nanoribbons are expected to show better carrier mobility, significant light capture and stronger mechanical properties, thereby increasing their advantages in the functionality of optoelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a characterization diagram of Cs4PbBr6 nanocrystals prepared by hot injection method in Example 1 of the present invention;
[0024] Figure 2 This is a diagram of the transformation process of non-fluorescent Cs4PbBr6 to fluorescent CsPbBr3 perovskite through phase transformation in Example 1 of the present invention;
[0025] Figure 3 Characterization diagram of the CsPbBr3 sample prepared in Example 1 of the present invention;
[0026] Figure 4 This is a stability comparison chart of the CsPbBr3 sample prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] In order to better understand the content of the present invention, the present invention will be further described below in conjunction with specific examples and drawings. The following examples are based on the technology of the present invention and provide detailed implementation methods and operating steps, but the scope of protection of the present invention is not limited to the following examples.
[0028] The present invention proposes a method for preparing water-stable all-inorganic cesium lead bromide perovskite nanobelts by interfacial phase transformation, which uses N-methylpyrrolidone as a solvent and oleic acid and oleylamine as surface ligands to prepare a cesium precursor solution and a lead bromide-containing reaction solution; the cesium precursor solution and the lead bromide-containing reaction solution are synthesized into a Cs4PbBr6 nanocrystal dispersion solution dispersed in n-hexane by a hot injection method; and then, at room temperature, the non-fluorescent Cs4PbBr6 nanocrystals dissolved in n-hexane undergo a phase transformation at the interface between the two phases to form fluorescent CsPbBr3 nanobelts that can be stably dispersed in water; the specific experimental steps are as follows:
[0029] (1) Preparation of a cesium precursor solution and a reaction solution containing lead bromide: 0.16 g (0.49 mmol) of cesium carbonate was dissolved in 0.5 mL of oleic acid and 8 mL of N-methylpyrrolidone, and the mixture was first evacuated to a vacuum environment at 120° C., and then heated in a nitrogen atmosphere to fully dissolve the mixture (heated to 150° C.), thereby obtaining a cesium precursor solution (i.e., cesium oleate solution); 0.188 mmol to 0.282 mmol (0.069 g to 0.103 g) of lead bromide was dissolved in 0.5 mL of oleic acid, 0.5 mL of oleylamine, and 5 mL of N-methylpyrrolidone, and the mixture was first evacuated to a vacuum environment at 120° C., and then heated in a nitrogen atmosphere (heated to 160° C. to 170° C.), thereby obtaining a reaction solution containing lead bromide (hereinafter referred to as the reaction solution).
[0030] (2) The cesium precursor solution and the reaction solution are reacted by a hot injection method: 0.4 mL to 0.6 mL of cesium oleate solution is added to the reaction solution at a certain temperature, and after sufficient reaction, the mixture is cooled in an ice water bath to obtain a reaction mixture.
[0031] (3) adding an antisolvent to treat the reaction mixture: adding an antisolvent to the reaction mixture in a volume ratio of 1:1, removing the supernatant after centrifugation, and obtaining a Cs4PbBr6 precipitation mixture; specifically, the antisolvent is one of ethyl acetate, acetone, methanol, and acetonitrile, and its function is to promote the formation of Cs4PbBr6 precipitation.
[0032] (4) Add a non-polar solvent to wash and disperse the Cs4PbBr6 precipitate mixture: Repeat the washing of the Cs4PbBr6 precipitate mixture with n-hexane solution for 2-3 times, centrifuge again to obtain a Cs4PbBr6 precipitate, and finally disperse the Cs4PbBr6 precipitate in n-hexane solvent to obtain a Cs4PbBr6 nanocrystal dispersion solution.
[0033] (5) Add the Cs4PbBr6 nanocrystal dispersion solution to a polar solvent to obtain a CsPbBr3 nanocrystal solution through a phase transition-water-induced conversion method: Place the Cs4PbBr6 nanocrystal dispersion solution and an equal volume of distilled water in two glass bottles, use a pipette to transfer the Cs4PbBr6 nanocrystal dispersion solution and slowly inject it into the pre-prepared distilled water along the wall of the container, and finally shake it vigorously to completely convert the Cs4PbBr6 nanocrystals into a CsPbBr3 nanocrystal solution dispersed in water. After standing and separating the liquid, a CsPbBr3 nanocrystal solution is obtained.
[0034] (6) Using high-purity water for centrifugal washing to obtain CsPbBr3 nanobelts: The CsPbBr3 nanocrystal solution is centrifuged to remove the supernatant to obtain the lower precipitate, which is then centrifuged and washed 2-3 times with high-purity water to obtain the CsPbBr3 nanobelts.
[0035] To investigate the stability of the prepared CsPbBr3 nanocrystal solution in aqueous solution, the CsPbBr3 nanocrystal solution can be stored at room temperature for 48 hours to observe whether it changes in the aqueous phase, and its fluorescence properties can be observed under ultraviolet light. The present invention uses a phase transition-water-induced conversion method to convert non-fluorescent Cs4PbBr6 nanocrystals dissolved in a non-polar solvent into fluorescent CsPbBr3 nanoribbons that can be stably dispersed in water through a phase transition at the interface between the two phases. Furthermore, in the presence of both the non-polar solvent and water, the CsPbBr3 nanoribbons maintain their green fluorescence over time, demonstrating good water stability. Furthermore, compared to three-dimensional nanocrystals, the size-dependent properties of perovskite nanoribbons are expected to exhibit improved carrier mobility, significant light capture, and stronger mechanical properties, thereby increasing their advantages in terms of the functionality of optoelectronic devices.
[0036] The present invention is described in detail below with specific embodiments:
[0037] Example 1:
[0038] (1) 0.16 g Cs2CO3 (0.49 mmol), 0.5 mL oleic acid and 8 mL N-methylpyrrolidone were placed in a 25 mL three-necked flask, vacuum treated at 120 ° C for 30 min, then nitrogen was introduced and the temperature was raised to 150 ° C until Cs2CO3 and oleic acid completely reacted to form cesium oleate solution. The cesium oleate solution was kept warm at 150 ° C for injection in the next step; 0.069 g PbBr2 (0.188 mmol), 0.5 mL oleic acid, 0.5 mL oleylamine and 5 mL N-methylpyrrolidone were added to another 25 mL three-necked flask, vacuum treated at 120 ° C for 30 min, then nitrogen was introduced and the temperature was raised to 170 ° C to completely dissolve the PbBr2 to obtain a reaction solution.
[0039] (2) Rapidly inject 0.4 mL of 150° C. cesium oleate solution into the reaction solution at 170° C., react for 6 to 8 seconds, and then quickly immerse the flask in an ice-water bath for rapid cooling to terminate the reaction, thereby obtaining a reaction mixture solution.
[0040] (3) Antisolvent ethyl acetate was added to the reaction mixture at a volume ratio of 1:1, and the mixture was centrifuged at 10300 rpm for 8 min. After centrifugation, the supernatant was removed to obtain a Cs4PbBr6 precipitation mixture.
[0041] (4) The Cs4PbBr6 precipitate mixture was washed three times with n-hexane solution, and then centrifuged at 10300 rpm for 3 min. The supernatant was discarded after centrifugation. Finally, the washed precipitate was dispersed in n-hexane solvent to obtain a Cs4PbBr6 nanocrystal dispersion solution. Figure 1 , wherein 1a is the XRD pattern (X-ray powder diffraction analysis pattern) of the Cs4PbBr6 nanocrystals prepared by the hot injection method in this embodiment, and it can be found that the prepared sample has a Cs4PbBr6 crystal phase structure; 1b is the UV-vis absorption spectrum (ultraviolet-visible absorption spectrum) of the Cs4PbBr6 nanocrystals prepared in this embodiment, and it can be concluded that the Cs4PbBr6 nanocrystals have an absorption peak at 314nm; 1c is a photograph of the Cs4PbBr6 powder sample prepared in this embodiment under natural light, and 1d is a photograph of the Cs4PbBr6 powder sample prepared in this embodiment under ultraviolet light with a wavelength of 365nm. It can be seen that the dried Cs4PbBr6 powder appears off-white under natural light, and only pitch black is observed under ultraviolet light irradiation, and no fluorescence phenomenon occurs.
[0042] (5) Place the Cs4PbBr6 nanocrystal dispersion solution and an equal volume of distilled water in two glass bottles. Use a pipette to transfer the Cs4PbBr6 nanocrystal dispersion solution and slowly inject it into the prepared distilled water along the container wall. Finally, shake it vigorously and let it stand to separate the liquid, thus obtaining a CsPbBr3 nanocrystal solution completely dispersed in water. Figure 2 , Figure 2 The following photographs illustrate the transformation process of non-fluorescent Cs4PbBr6 into fluorescent CsPbBr3 perovskite via a phase transition method in this example. 2a and 2b are photographs of the Cs4PbBr6 sample dispersed in n-hexane under natural light and ultraviolet light, respectively; 2c and 2d are photographs of the water-n-hexane interface after water-induced formation of CsPbBr3 under natural light and ultraviolet light, respectively; and 2e and 2f are photographs of CsPbBr3 uniformly dispersed in water under natural light and ultraviolet light, respectively. When the Cs4PbBr6 sample dispersed in n-hexane is placed on top of the water, a yellow substance is observed at the n-hexane-water interface. This substance emits green fluorescence under ultraviolet light and completely disperses in the water after vigorous shaking and allowing the sample to stand for a period of time.
[0043] (6) The CsPbBr3 nanocrystal solution was centrifuged, and the supernatant was discarded to obtain the lower precipitate. The lower precipitate was then centrifuged and washed three times with high-purity water to obtain CsPbBr3 nanobelts. Figure 3 , wherein 3a is the XRD pattern (X-ray powder diffraction analysis pattern) of the CsPbBr3 sample prepared in this embodiment, and it can be found that the prepared sample has a CsPbBr3 crystal structure; 3b is the UV-vis absorption spectrum (ultraviolet visible absorption spectrum) and fluorescence spectrum of the CsPbBr3 sample prepared in this embodiment, and it can be concluded that the CsPbBr3 sample has a weak absorption peak at 510nm, and the corresponding fluorescence peak is located at 518nm; 3c and 3d are the CsP prepared in this embodiment, respectively. The TME (transmission electron microscopy) and HRTEM (high-resolution transmission electron microscopy) images of the CsPbBr3 sample show that the CsPbBr3 prepared by phase transformation in this embodiment is a nanobelt with a small size. Figures 3e and 3f are photos of the CsPbBr3 powder sample prepared in this embodiment under natural light and ultraviolet light, respectively. It can be seen that, unlike Cs4PbBr6, the powder sample of CsPbBr3 is yellow under natural light and emits bright green fluorescence under ultraviolet light.
[0044] See also Figure 4The CsPbBr3 nanocrystal solution was stored at room temperature for 48 hours to observe its changes in the aqueous phase. 4a and 4b are photos showing the stability of the CsPbBr3 sample prepared in this example (the upper layer of all solutions is n-hexane and the lower layer is water); 4a and 4b were taken under natural light and ultraviolet light, respectively. It can be concluded that the CsPbBr3 sample can not only be dispersed in water and show good water stability, but its green fluorescence can still be well maintained after 48 hours.
[0045] Example 2:
[0046] (1) 0.16 g Cs2CO3 (0.49 mmol), 0.5 mL oleic acid and 8 mL N-methylpyrrolidone were placed in a 25 mL three-necked flask, vacuum treated at 120 ° C for 30 min, then nitrogen was introduced and the temperature was raised to 150 ° C until Cs2CO3 and oleic acid completely reacted to form cesium oleate solution. The cesium oleate solution was kept at 150 ° C for injection in the next step; 0.086 g PbBr2 (0.235 mmol), 0.5 mL oleic acid, 0.5 mL oleylamine and 5 mL N-methylpyrrolidone were added to another 25 mL three-necked flask, vacuum treated at 120 ° C for 30 min, then nitrogen was introduced and the temperature was raised to 165 ° C to completely dissolve the PbBr2 to obtain a reaction solution.
[0047] (2) Rapidly inject 0.5 mL of 150° C. cesium oleate solution into the reaction solution at 165° C., react for 6 to 8 seconds, and then quickly immerse the flask in an ice-water bath for rapid cooling to terminate the reaction, thereby obtaining a reaction mixture solution.
[0048] (3) adding antisolvent acetone to the reaction mixture in a volume ratio of 1:1, centrifuging at 10300 rpm for 8 min, and removing the supernatant after centrifugation to obtain a Cs4PbBr6 precipitation mixture.
[0049] (4) The Cs4PbBr6 precipitate mixture was washed twice with n-hexane solution, and then centrifuged at 10300 rpm for 3 min. The supernatant was discarded after centrifugation, and the washed precipitate was dispersed in n-hexane solvent to obtain a Cs4PbBr6 nanocrystal dispersion solution.
[0050] (5) Place the Cs4PbBr6 nanocrystal dispersion solution and an equal volume of distilled water in two glass bottles. Use a pipette to transfer the Cs4PbBr6 nanocrystal dispersion solution and slowly inject it into the pre-prepared distilled water along the wall of the container. Finally, shake it vigorously and let it stand to separate the liquid, thereby obtaining a CsPbBr3 nanocrystal solution completely dispersed in water.
[0051] (6) The CsPbBr3 nanocrystal solution was centrifuged and the supernatant was discarded to obtain the lower precipitate, which was then centrifuged and washed three times with high-purity water to obtain the product CsPbBr3 nanobelt.
[0052] The CsPbBr3 nanocrystal solution prepared above was stored at room temperature for 48 hours to observe its changes in the aqueous phase. It was found that the CsPbBr3 nanocrystals could be dispersed in water and showed good water stability, and their green fluorescence could still be well maintained after 48 hours.
[0053] Example 3:
[0054] (1) 0.16 g Cs2CO3 (0.49 mmol), 0.5 mL oleic acid and 8 mL N-methylpyrrolidone were placed in a 25 mL three-necked flask, vacuum treated at 120 ° C for 30 min, then nitrogen was introduced and the temperature was raised to 150 ° C until Cs2CO3 and oleic acid completely reacted to form cesium oleate solution. The cesium oleate solution was kept warm at 150 ° C for injection in the next step; 0.103 g PbBr2 (0.282 mmol), 0.5 mL oleic acid, 0.5 mL oleylamine and 5 mL N-methylpyrrolidone were added to another 25 mL three-necked flask, vacuum treated at 120 ° C for 30 min, then nitrogen was introduced and the temperature was raised to 160 ° C to completely dissolve the PbBr2 to obtain a reaction solution.
[0055] (2) Rapidly inject 0.6 mL of 150° C. cesium oleate solution into the reaction solution at 160° C., react for 6 to 8 seconds, and then quickly immerse the flask in an ice-water bath for rapid cooling to terminate the reaction, thereby obtaining a reaction mixture solution.
[0056] (3) adding antisolvent methanol to the reaction mixture at a volume ratio of 1:1, centrifuging at 10300 rpm for 8 min, and removing the supernatant after centrifugation to obtain a Cs4PbBr6 precipitation mixture.
[0057] (4) The Cs4PbBr6 precipitate mixture was repeatedly washed three times with n-hexane solution, and then centrifuged at a speed of 10300 rpm for 3 minutes. After centrifugation, the supernatant was discarded and the washed precipitate was dispersed in n-hexane solvent to obtain a Cs4PbBr6 nanocrystal dispersion solution.
[0058] (5) Place the Cs4PbBr6 nanocrystal dispersion solution and an equal volume of distilled water in two glass bottles. Use a pipette to transfer the Cs4PbBr6 nanocrystal dispersion solution and slowly inject it into the pre-prepared distilled water along the wall of the container. Finally, shake it vigorously and let it stand to separate the liquid to obtain a CsPbBr3 nanocrystal solution completely dispersed in water.
[0059] (6) The CsPbBr3 nanocrystal solution is centrifuged and the supernatant is discarded to obtain the lower precipitate, which is then centrifuged and washed three times with high-purity water to obtain the CsPbBr3 nanobelt.
[0060] The CsPbBr3 nanocrystal solution prepared above was stored at room temperature for 48 hours to observe its changes in the aqueous phase. It was found that the CsPbBr3 nanocrystals could not only be dispersed in water and showed good water stability, but their green fluorescence could still be well maintained after 48 hours.
[0061] The present invention can have other embodiments according to the above preparation method, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any person skilled in the art to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention shall still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing water-stable all-inorganic cesium lead bromine perovskite nanobelts by interfacial phase transformation, characterized in that: The following steps are involved: (1) preparing a cesium precursor solution and a reaction solution containing lead bromide; The preparation method of the cesium precursor solution is as follows: 0.16 g (0.49 mmol) of cesium carbonate is dissolved in 0.5 mL of oleic acid and 8 mL of N-methylpyrrolidone, vacuum treated at 120° C. for 30 min, and then heated in a nitrogen atmosphere to fully dissolve the cesium carbonate to obtain a cesium oleate solution, i.e., a cesium precursor solution. The temperature during the above heating treatment is 150° C. The cesium precursor solution is kept warm at 150° C. for injection in the next step; The preparation method of the reaction solution containing lead bromide is as follows: 0.188 mmol (0.069 g) of lead bromide is dissolved in 0.5 mL of oleic acid, 0.5 mL of oleylamine and 5 mL of N-methylpyrrolidone, firstly vacuum treated at 120° C. for 30 min, and then heated under a nitrogen gas atmosphere to obtain a reaction solution containing lead bromide, wherein the temperature during the heating treatment in the preparation method is 170° C.; (2) quickly injecting 0.4 mL of a 150° C. cesium precursor solution into the 170° C. reaction solution, reacting for 6 to 8 seconds, and then rapidly immersing the flask in an ice water bath to rapidly cool the flask to terminate the reaction, thereby obtaining a reaction mixture solution; (3) adding an equal volume of an antisolvent to the reaction mixture, centrifuging at 10300 rpm for 8 min, removing the supernatant after centrifugation to obtain a Cs4PbBr6 precipitation mixture; the antisolvent is ethyl acetate; (4) adding n-hexane solution to wash the Cs4PbBr6 precipitate mixture, washing and centrifuging for multiple times to obtain Cs4PbBr6 precipitate, dispersing the Cs4PbBr6 precipitate in n-hexane solvent to obtain a Cs4PbBr6 nanocrystal dispersed solution; (5) slowly injecting the Cs4PbBr6 nanocrystal dispersion solution into an equal volume of distilled water, shaking it vigorously and then allowing the solution to stand to separate to obtain a CsPbBr3 nanocrystal solution; (6) Use high-purity water to centrifuge and wash the CsPbBr3 nanocrystal solution to obtain CsPbBr3 nanobelts.
Citation Information
Patent Citations
An all-inorganic halide perovskite nanocrystal and its preparation method
CN109264771B
Preparation method of air-stable all-inorganic mixed halogen perovskite nanowires
CN111139518A
Preparation method and application of totally-inorganic perovskite nanorod
CN108046314A
All-inorganic halogen perovskite nano-crystal and preparation method thereof
CN109264771A
Zero-dimensional perovskite caesium lead bromine nanosheet and preparation method and application thereof
CN109777416A